DEPENDENCE OF MILK YIELD OF COWS OF SIMMENTAL BREED ON UDDER FORMS - ASHIROV, M. D; F. R. SATTAROV; F. B. BAHRIDDINOV (Proceedings of The ICECRS, 2020)
In the research, it was determined that the milk yield of cows from abroad of Simmental breed depends on the udder forms in the conditions of Uzbekistan.. Milk production type with The Shape of the pelvic udder it has been noted that cows have achieved a significant advantage in milk yield from cows with The Shape of a cup and round udder. It was noted that the selection-breeding work on the udder forms of cows in the breeding of cattle of Simmental breeds is an important factor in the creation of high-yielding dairy herds. Also, the udder index of cows of Group I of the type of milk production and the milk yield rate were higher than that of cows in groups II and III, these data indicate that the udder of cows of Group I was developed proportionally and was well adapted to modern milking equipment.